IL-6 variant is associated with metastasis in breast cancer patients. - Chike O Abana; Brian S Bingham; Ju Hwan Cho; Amy J Graves; Tatsuki Koyama; Robert T Pilarski; A Bapsi Chakravarthy; Fen Xia (PLoS ONE)
Introduction Although tumor metastases remain significant drivers of mortality, the genetic factors that increase the risks of metastases are not fully identified. Interleukin 6 (IL-6) has emerged as an important factor in breast cancer progression with IL-6 single nucleotide polymorphism (SNP) variants shown to affect survival. We hypothesized that SNPs of the IL-6 promoter at rs1800795 in breast cancer patients are associated with distant metastases. Methods We performed an initial case-control study using Vanderbilt University Medical Center's BioVU, a genomic biobank linked to de-identified electronic medical records in the Synthetic Derivative database, to identify germline SNPs that may predict the development of metastatic disease to any site from any solid tumor including breast cancer. We identified a SNP in IL-6: rs1800795 to be of significance and evaluated this finding using a separate, matched-pair cohort of breast cancer patients with and without metastases from The Ohio State University Wexner Medical Center. Results The initial study suggested that GG relative to CG at rs1800795 (OR 1.52; 95% CI 1.14-2.02; p = 0.004) was significantly associated with the development of metastases. This association was also observed in the Ohio State University cohort (OR 2.23; 95% CI 1.06-4.71; p = 0.001). There were no significant relationships between rs1800795 status and any patient or tumor characteristics, including estrogen receptor status. Conclusions These findings suggest that GG SNP at IL-6: rs1800795 may indicate an increased risk of metastasis of primary breast cancer. Further studies in larger population sets are warranted as advanced screening and prophylactic intervention might be employed in GG carriers.